Determinants of Early Initiation of Breastfeeding in Lamongan Public Health Center - Muthoharoh, Husnul (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The World Health Organization (WHO) and United Nations Children's Fund (UNICEF) recommend initiation of breastfeeding within the first hour of life. This research aimed to investigated the determinants of breastfeeding practices in Lamongan Public Health Center. This study used an observational analytic research design with a cross-sectional approach. The population in this study were all mothers giving birth at the Lamongan Public Health Center when the study was running in May-July 2020. The sampling technique used total sampling. The sample in this study are 43 people. The factors associated with the implementation of early breastfeeding initiation were knowledge about early initiation of breastfeeding (p value = 0.000) and family support (p value = 0.006). It is recommended that childbirth service providers provide education to families before childbirth in order to facilitate the implementation of early initiation of breastfeeding.